Chloroquine and Hydroxychloroquine in Treatment of Coronavirus Disease-19 - Lidija Poposka; Irena Mitevska (Scientific Foundation SPIROSKI, 2020)
At present, we are facing coronavirus disease (COVID)-19 pandemic caused by the severe acute respiratory syndrome coronavirus-2 with several treatment choices and reports of different treatment outcomes. Chloroquine and hydroxychloroquine use for the management of severely ill patients started as a quite enthusiastic treatment option, following several small clinical trials, case series reports, public authorities, and media affirmation. However, the evidence we have so far is conflicting and some national societies and professional institutions implicate that we should wait for definite treatment recommendations until there are solid data for or against the use of these drugs. Until we have more powerful evidence in our hands, we should be aware of safety issues of the old drugs for the new application in the emergency state we are facing today with the COVID-19 pandemic. We performed a concise review of strengths, limitations, and awareness for chloroquine and hydroxychloroquine use for COVID-19 infection treatment based on the evidence the science has today.
Keywords: COVID-19; drugs